A Metabolism Toolbox for CAR T Therapy - Xu, Xuequn; Gnanaprakasam, J. N. Rashida; Sherman, John; Wang, Ruoning (Frontiers in Oncology, 2019)
Abstract The adoptive transfer of T cells expressing chimeric antigen receptors (CARs) through genetic engineering is one of the most promising new therapies for treating cancer patients. A robust CAR-T cell-mediated anti-tumor response requires the coordination of nutrient and energy supplies with CAR-T cell expansion and function. However, the high metabolic demands of tumor cells compromise the function of CAR-T cells by competing for nutrients within the tumor microenvironment (TME). To substantially improve clinical outcomes of CAR-T immunotherapy while treating solid tumors, it is essential to metabolically prepare CAR-T cells to overcome the metabolic barriers imposed by the TME. In this review, we discuss a potential metabolism toolbox to improve the metabolic fitness of CAR T cells and maximize the efficacy of CAR T therapy.